Anatomía comparativa del xilema de la rama de dos especies forestales del arboretum el huayo en Puerto Almendra, Loreto-Perú, 2022 - Camus Loayza, Cristina Wieslawa (2023)
In the present study, the macroscopic and microscopic description and comparison of the xylem of the branch of Tovomita krukovii A. C. Sm "chullachaqui caspi" and Remijia pedunculata (H. Karst.) Flueck "cascarilla" was carried out. The branch samples were collected in the Arboretum "El Huayo" of CIEFOR Puerto Almendra, and then taken to the Laboratory of Anatomy and Wood Technology of the FCF of the UNAP. Similar and differentiating anatomical characteristics were determined and the xylem of the branch of both species was classified. For this work, the procedure indicated by Valderrama (1986) and IAWA (1989) was followed for the preparation of histological slides and individual cells and their anatomical description. Similar and different characteristics were found in the branch xylem of the two species, with 40.5% of similar characteristics. Of the total quantitative anatomical features evaluated statistically at 95% probability, 63% of these features had significant differences.